Environmental Interpretation of a marine trail in Palito, Island of Chira, Puntarenas (Biocenosis, 2012)
Environmental Interpretation is a form of non-formal environmental education that is developed with non-captive audience, whose participation is voluntary. Cuerderos Fishermen’s Association of Palito, Chira (Asopecupachi) participates in the Management of a Responsible Fishing Marine Area (AMPR) and is making inroads into the rural community tourism. This article presents the experience gained with the Asopecupachi, where through interpretive planning was achieved the design of a marine interpretive trail in the AMPR and the training of fishermen as guides to the attention of tourists inside. This was done based on the resources, needs and life stories of fishermen and the AMPR.
Keywords: Non-formal environmental education; Marine interpretative trail; Hand-line fishing